Indonesia PENGARUH JUMLAH HOTEL TERHADAP PENDAPATAN ASLI DAERAH (PAD) MELALUI PAJAK HOTEL SEBAGAI INTERVENING (Studi Kasus di Kota Yogyakarta Tahun 2013-2016) - Flora Trivonia Solot (JURNAL EKOBIS DEWANTARA, 2018)
The higher the role of the Original Revenue is a mirror of the success of the efforts or the level of regional capability in financing the implementation of governance and development. This study aims to determine the influence of the number of hotels, hotel taxes as intervening variables, and local revenue. This study uses secondary data. Hypothesis testing uses purposive sampling method and technical data analysis for local revenue as dependent variable (Y), number of hotel as independent variable (X), and hotel tax as intervening variable using path analysis. The results of this study conclude: 1) Number of hotels have a significant positive effect on local revenue with the value of t-count 4,570> t-table 1,679 significant value 0.000. 2) Number of hotels have a significant positive effect on hotel taxes with t-value of 7,938> t-table 1,679 significant value 0,000. 3) Hotel tax has a significant positive effect on the local income with the value of t-count 4,644> t-table 1,679 significant value 0,000. 4) The variable of the number of hotels to the original revenues of 0,559 and the indirect effect of 0.9884. These results indicate that indirectly the number of hotels significantly influence the local revenue through the hotel tax as an intervening.